University Life Happiness of Local and International Students in Malaysia : The Case of University Utara Malaysia - Muhammad Baqir, Abdullah (2011)
This thesis examines the level of university life happiness of local and international students using a quota sample of Universiti Utara Malaysia students. The sample was collected using self-administered questionnaire which collected total of 354 local students and 108 international students. The responses rates are 88.5% and 72% for local and international students respectively. Result of descriptive analysis show that on average, local and international students are happy with their university life. However, relatively, local students have higher happiness compared to international students. Result of regression analysis show that student’s (local and international) relationship with UUM people is the important determination of their university life happiness. However, comparatively, the significant determination of university life happiness of local and international students are varies. For international students, one of important determinants is their English language proficiency (spoken). For local students, one of the most important determinants is frequency of prayer that they have performed. Other determinants of university life happiness for local students are frequency get illness and sleep quality. Other determinants of university life happiness for international students are mothers’ level of education, number of friends, communication problems, writing skill and speaking skill of Malay. The policy implications and suggestions one discussed based on this finding. In particular, it is suggested that include the communication skills which we the significant determinants at their happiness.